Nutritional and Physico-chemical Qualities of Popular Retail Cuts of Large White Yorkshire pig - Chowdhury, S. J.; Chakraborty, R.; Biswas, S.; Sahoo, S.; Das, S. K. (Journal of Meat Science, 2016)
Four popular retail cuts of Large White Yorkshire pigs (16 nos.) weighing 80 to 90 Kg body weight were analysed for the proximate composition, fatty acids, cholesterol, energy, minerals and other physico-chemical composition. The mean content (%) of moisture (58.62 ± 0.168 to 74.77 ± 0.165), protein (15.73 ± 0.109 to 20.85 ± 0.131), lipids (3.45 ± 0.106 to 22.94 ± 0.132), ash (0.83 ± 0.017 to 1.01 ±0.015), monounsaturated fatty acids (1.38 ± 0.019 to 9.25 ± 0.034 ), poly unsaturated fatty acids (0.52 ± 0.021 to 3.06± 0.025), saturated fatty acids (1.18 ± 0.024 to7.34 ± 0.032) of raw cuts were recorded. Further, cholesterol (mg/100g) (65.99 ± 0.133to 79.83 ± 0.106), energy content (kcal/100g) (130.34 ± 1.03 to 270.36 ± 1.24) and mineral compositions (mg/100g) viz., iron (0.45 ± 0.015 to 0.95 ± 0.015), calcium (6.45 ± 0.152 to 20.43 ± 0.160) sodium (45.58 ± 0.209 to 78.71 ± 0.135) and potassium (238.31 ± 0.876 to 398.51 ± 0.989) were also carried out. Physico-chemical parameters like fiber diameter (µm) (45.24 ± 0.151 to 51.01 ± 0.156), sarcomere length (µm) (2.64 ± 0.015 to 2.79 ± 0.012), hydroxyproline (mg/100g) (1.26 ± 0.014 to 1.41 ± 0.013), pH (5.63 ± 0.012 to5.77 ± 0.013) and water holding capacity (%) (43.03 ± 0.091 to 49.68 ± 0.090) of raw meat cuts werealso recorded. Significant difference (p<0.05) has been observed for almost all the proximate composition and fatty acids and energy content,mineral and other physico-chemical compositions parameters of meat, location wise. On cooking, all the parameters increased except moisture, sodium,potassium, fiber diameter, sarcomere length and water holding capacity, which decreased significantly (p<0.05) as compared to their raw counter parts.